The impacts of product characteristics and regulatory environment on smokers' preferences for tobacco and alcohol: Evidence from a volumetric choice experiment. - Shaoying Ma; Ce Shang; Vuong V Do; Jidong Huang; Terry F Pechacek; Scott R Weaver (PLoS ONE)
Objective Concurrent use of alcohol and cigarettes is well-documented in the literature. However, it is unclear how e-cigarette regulations in a growing number of localities impact the use of tobacco and alcohol in the US. This study aims to evaluate the impacts of excise taxes, tobacco use restrictions in restaurants/bars, and availability of alcohol flavor in e-cigarettes on tobacco consumption, and their cross impacts on alcohol consumption. Method A total of 181 US adult smokers who were using e-cigarettes and consuming alcohol participated in online volumetric choice experiments and reported on the quantity they would purchase among cigarettes, closed-system e-cigarettes, beer, and one other alcohol product (wine/liquor) under varying policy scenarios. Results Estimated own-price elasticities of demand for beer, liquor/wine, and cigarettes were -0.10, -0.11, and -0.16, respectively (p <  0.001). Higher beer (cross-price elasticity =  0.13) and liquor/wine prices (cross-price elasticity =  0.05) increased e-cigarette consumption (p <  0.05). If e-cigarettes were allowed in bars/restaurants, their consumption increased by 2.4 units (p <  0.001), and if cigarettes were allowed in bars/restaurants, e-cigarette consumption increased by 1.9 units (p <  0.01), relative to the mean consumption level. Greater reported weekly spending on alcohol and/or tobacco was associated with higher consumption of all products (p <  0.001). Conclusions Higher taxes or prices may reduce the consumption of beer, liquor/wine, and cigarettes. E-cigarettes are economic substitutes for alcohol among smokers who are currently drinking and using e-cigarettes. Regulating tobacco indoor use will have an impact on e-cigarette consumption.